Hypereosinophilic syndrome with elevated IgG4 and T-cell clonality: A report of two cases - Huang Meichun; Wang Limin; Li Xiuxiu; Lu Ying (Open Life Sciences, 2025)
In some cases, higher IgG4 levels are accompanied by increased circulating IgE, higher eosinophil counts, and various autoantibodies. Among these cases, IgG4-related disease (IgG4-RD) is one of the most frequently diagnosed conditions. This study reported two particularly complex and rare cases of hypereosinophilic syndrome (HES) associated with elevated IgG4 and T-cell clonality. The first case involved T-cell clonality complicated by HES and IgG4-RD, presenting with clinical features resembling eosinophilic granulomatosis with polyangiitis (EGPA). Laboratory findings showed a serum IgG4 concentration of 8.74 g/L, an IgG4/IgG ratio of 40.58%, and positive results for P-anti-neutrophil cytoplasmic antibodies (ANCA) and myeloperoxidase-ANCA. Renal biopsy findings were consistent with IgG4-related interstitial nephritis. However, routine hematological testing revealed a markedly elevated eosinophil count of 14.75 × 109/L and eosinophilic infiltration in both lymph nodes and kidney tissue. Furthermore, monoclonal rearrangements of the T-cell receptor gamma and delta genes were identified. The second patient was ultimately diagnosed with HES with elevated IgG4 and T-cell clonality, with an elevated IgG4 concentration of 2.458 g/L and an eosinophil count of 14.75 × 109/L. In conclusion, in cases presenting with elevated IgG4 levels and hypereosinophilia, further pathological and genetic evaluations may be essential to guide appropriate and timely treatment, improving patient prognosis.